Effects of Memorizing Al-Qur’an On Mathematical Reasoning - Rosdiana IM; Ikrimah . (Daya Matematis: Jurnal Inovasi Pendidikan Matematika, 2020)
This study was conducted to investigate the effects of memorizing Al-Qur’an on the ability of mathematical reasoning. The population of this study was all students of grade IX of Al Fityan Gowa Integrated Islamic JunioR High School, Indonesia, totaling 93 people. The sampling technique used is saturated sampling. Data on mathematical reasoning ability was obtained from the results of tests on mathematical reasoning and the ability to memorize Al-Qur’an was taken from the final score of Tahfidz (memorization) Al-Qur’an subjects. Data were analyzed by simple linear regression. The result revealed that there was a significant relationship between memorizing Al-Qur’an and the ability of mathematical reasoning. The regression linear model was able to be built. The coefficient of regression is 1.231. The score indicated that every increase of one unit of memorizing Al-Qur’an will increase the ability of mathematical reasoning by 1,232 points. The coefficient of determination is 0.449 that indicated the ability of mathematical reasoning was influenced by the memorization Al-Qur’an by 20.2%.